Use of NIR spectroscopy to monitor substrate biodegradation lignocellulosics by Pleurotus - Nascimento, Cristiano Souza do; Sales-Campos, Ceci; Nascimento, Claudete Catanhede do; Araujo, Roberto Daniel de; Abreu, Raimunda Liége Souza de; Cruz, irineide de Almeida (Comunicata Scientiae, 2023)
Understand the process of biodegradation of lignocellulosic material as its chemical composition is key properties for enhancing the cultivation of edible mushrooms, which seek in lignin and other carbon source carbohydrates. The purpose of this study was to monitor polysaccharide and lignin degradation caused by Pleurotus ostreatoroseus on different agroindustrial substrates using near infrared spectroscopy (NIR). Sawdust substrates of Marupá and Cajuí wood, banana pseudostem fibers, enriched with bran of cereals were formulated (WB and MWB). Of the 12 formulations elaborated, eight were submitted to biodegradation of P. ostreatoroseus over a period of 49 days (Residual substrate), and four formulations maintained in natura (Initial substrates), where each treatment was formed by 10 replicates totaling n = 120. Spectra were obtained from the substrates before and after cultivation in FT-NIR system in the region between 10,000 and 4,000 cm-1 and the index degradation of lignocellulosic compounds was determined (LDI and PDI). Through Fourier transform near infrared spectroscopy was it is possible to observe the degradation of polysaccharides and lignin in the substrates grown with the fungus P. ostreatoroseus. In the residual substrate Marupá+WB-POSP was the highest lignin degradation index (LDI = 9.26%). While whereas for the PDI (Polysaccharide degradation index), the highest degradation (7.12%) was observed in the residual substrate Cajuí+MWB-POAM. Through analysis of the absorption bands, it was possible to observe the degradation of structures/bonds characteristics of lignocellulosic residues. The NIR model for degradation of lignocellulosic compounds was more effective in predicting “lignin degradation” in the spectral range 6,350-7,308 cm-1